Peer Effects and Rural Households’ Online Shopping Behavior: Evidence from China - Jiaxi Zhou; Guoxiong Zhao; Liuyang Yao (Agriculture, 2025)
Amid the rapid expansion of the digital economy, online shopping has become increasingly common among rural households in China, yet the social interaction mechanisms driving such behavior remain insufficiently explored. This study examines the impact of peer effects on farmers’ online shopping behavior using data from the China Family Panel Studies (CFPS) covering the years 2014 to 2022. A Logit model is applied to estimate peer influence, and interaction terms are introduced to assess the moderating roles of land assets and social expenditures. The results reveal that peer behavior significantly increases the likelihood of rural households participating in online shopping, with the effect being particularly strong among low-income, less-educated households and those in western regions. Additionally, both land-rich households and those with higher social expenditures demonstrate greater responsiveness to peer influence. These findings highlight the importance of local social interaction in shaping rural online shopping behavior and provide theoretical and practical implications for digital inclusion and rural e-commerce strategies.